Adoption of Green Operation Strategies and Best Practices in the Era of Sustainable Development Goals: Study of Public Limited Hospitals in Indonesia - Purwanto, Marini; Ellitan, Lena (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2025)
This research aims to identify best practices for implementing green (environmental friendly) operations strategies in hospitals. A total of 9 public l limited hospital companies in Indonesia were investigated. The data source is the annual sustainability report taken from the publication of Sustainability Reporting on Index (GRI) and the implementation of POJK 03/51/2017. This research adopts a quantitative content analysis method of sustainability reports accompanied by qualitative as well as evaluative analysis. The findings of this research found 4 main taxonomies of green operations strategies in hospitals, namely good waste management, waste prevention, water and wastewater management, energy conversion, and emission reduction. This research is the preliminary research regarding best practice environmentally friendly operating strategies at public l limited hospitals in Indonesia with the support of sustainability report data implemented in 2018 in Indonesia based on POJK 51 of 2017 regulations, this is an important issue in the development of further research where in the future research will also can link the other two pillars of sustainability to find the relationship between environmental performance and social or financial performance.